Pengaruh tangibility, profitability, liquidity, firm size dan non debt taxshield terhadap capital structure pada sektor pertanian - DEDE BADRU TAMAM; SATRIYO WIBOWO (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to test and analyze empirically the influence of tangibility, profitability, liquidity, firm size and non-debt tax shield toward capital structure. The object of this research is agriculture sector companies that listed in Indonesia Stock Exchange period 2008-2014. The purposive sampling is used as sampling technique, where 14 companies met the criteria and were analyzed using eviews 8 panel data regressions with random effect model to test the hypothesis. The results of this research shows that liquidity and firm size influence capital structure, while profitability, tangibility and non-debt tax shield do not influence capital structure.